Estudo das relações filogenéticas supraespecíficas de Hybothoracini Boucek (Hymenoptera, Chalcididae, Haltichellinae) - Araujo, Bruno Cancian de (2014)
The first supraespecific cladistic analysis forHybothoracini is presented. 21 genera and 92 OTUs are tested. Based on 91 morphological characters, 11 parsimony analysis were performed, one with equal weighting and 10 with implied weighting for k values between 1 and 300. Equal weighting analyzes resulted in four equally parsimonious trees, and one strict consensus tree was generated. The 10 analyzes of implied weighing generated one tree each, with basically three different topologies for k ranging from 1 to 10, from 16 to 50, and from 100 to 300. Hybothoracini is monophyletic in all analyzes and includes Tropimeris and Zavoya as proposed by Wijesekara (1997). The following genera are maintained: Hastius Schmitz, Hybothorax Ratzeburg, Irichohalticella, Cameron, Lasiochalcidia Masi, Nearretocera Girault, Nipponochalcidia Habu, Notaspidiella Boucek, Notaspidium Dalla Torre, Proconura Dodd, Psilochalcis Kieffer, Schwarzella Ashmead, Solenochalcidia Steffan, Steninvreia Boucek, XenarretoceraGirault, Tropimeris Steffan. Ninenew generic synonyms are proposed: HayatiellaNarendran, new. syn. andNeohybothorax Nikol'skaya, new. syn. under Hybothorax 10Ratzeburg; Bucekia Steffan, new. syn. andIndoinvreia Roy & Farooqi, new. syn. under Lasiochalcidia Masi; Halsteadium Boucek, new. syn. under Notaspidium Dalla Torre; Cephalochalcidia Nikol’skaya, new. syn., Euchalcidiella Masi, new. syn., Hyperchalcidia Steffan, new. syn., Peltochalcidia Steffan, new. syn. under Xenarretocera Girault. Thirty-two new combinations and one combination revalidation are proposed: Hybothorax aligarhensis (Narendran, 1989), new. comb., Hybothorax hetera Walker, 1834,new. comb., Hybothorax imitator (Nikol'skaya, 1960) new. comb., Lasiochalcidia bouceki (Nikol'skaya, 1960) new. comb., Lasiochalcidia differens Boucek, 1949, comb. rev., Lasiochalcidia dissimilis (Nikol'skaya, 1960) new. comb., Psilochalcis erythropus (Cameron, 1897) new. comb., Lasiochalcidia turkomana (Nikol'skaya, 1960) new. comb., Lasiochalcidia carinigena (Cameron, 1907) new. comb., Lasiochalcidia zdenekia (Roy & Farooqi, 1984) new. comb., Notaspidium alterum (Boucek, 1992) new. comb., Notaspidium petiolatum (Boucek, 1992) new. comb., Proconura menoni (Roy & Farooqi, 1984) new. comb., Psilochalcis merita (Nikol'skaya, 1960) new. comb., Xenarretocera capitata (Nikol'skaya, 1960) new. comb., Xenarretocera levis (Nikol'skaya, 1960) new. comb., Xenarretocera bardiensis (Masi, 1929b) new. comb., Xenarretocera benoisti (Steffan, 1948) new. comb., Xenarretocera capensis (Steffan, 1948) new. comb., Xenarretocera clypeata(Boucek, 1952) new. comb., Xenarretocera frontalis (Askew, 1994) new. comb., Xenarretocera nigerrima (Masi, 1929c) new. comb., Xenarretocera nitens (Steffan, 1948) new. comb., Xenarretocera oranensis (Boucek, 1952) new. comb., Xenarretocerapatrizii (Masi, 1929d) new. comb., Xenarretocerapopovi (Nikol'skaya & Kyao, 1954) new. comb., Xenarretocera schoutedeni (Steffan, 1954) new. comb., Xenarretocera shestakovi (Nikol'skaya, 1960) new. comb., Xenarretocera soudanensis (Steffan, 1951a) new. comb., Xenarretocera tadzhika (Nikol'skaya, 1960) new. comb., Xenarretocera usta (Grissell & Schauff, 1981) new. comb., Xenarretocera zarudnyi(Nikol'skaya, 1960) new. comb.